Case Report: Thromboelastography for uremic thrombocytopathy in a patient with COVID-19 - Kannan, Lakshmi; Raj, Rishi (Frontiers in Nephrology, 2022)
Uremia causes several biochemical and physiological impairments that result in the accumulation of toxins with multiple clinical effects. Bleeding is one of the most common complications of acute and chronic renal failure. The pathogenesis of uremic bleeding is multifactorial, of which uremic thrombocytopathy is the most described clinically. Various tests have been used to evaluate bleeding diathesis in these patients including bleeding time, prothrombin time, activated partial thromboplastin time, and international normalized ratio, but there are only a few studies that use thromboelastography as a point-of-care test to identify platelet dysfunction. In addition, COVID-19 increases hemorrhagic complications due to platelet dysfunction or hemostasis exhaustion. COVID-19 could also potentially cause platelet dysfunction as a secondary consequence of acute kidney injury. There are only a few studies reporting the use of thromboelastography in COVID-19–induced hypercoagulability, but not in diagnosing or managing platelet-related abnormalities. We present a patient with COVID-19 who developed acute kidney injury in the hospital and retroperitoneal hemorrhage from uremic platelet dysfunction. We used point-of-care thromboelastography with platelet mapping to determine uremic platelet dysfunction.